Isolation of Endophytic Pseudomonas Strains from Papaya Leaves and Their Extracellular Enzyme Production and Antioxidant Profile - Sarjono, Purbowatiningrum Ria; Choirunnisa, Nur Fadilla; Triwijayanti, Yunita; Salsabila, Salsabila; Asy’ari, Mukhammad; Ngadiwiyana, Ngadiwiyana; Ismiyarto, Ismiyarto; Prasetya, Nor Basid Adiwibowo; Andriani, Yosie (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
Endophytic bacteria, symbiotic microorganisms residing in plant tissues, produce bioactive compounds similar to host plants, such as antioxidants. These antioxidants are crucial in combating free radicals linked to degenerative diseases. This study isolates and characterizes two endophytic bacterial strains from papaya leaves, exploring their enzymatic and antioxidant activities. Two isolates of endophytic bacteria from papaya leaves were obtained, F1-A and F1-B. F1-A endophytic bacteria are types of monobacilli, Gram-positive bacteria. F1-B endophytic bacteria are types of Bacilli. Using 16S rRNA analysis, both isolates were predicted to belong to the Pseudomonas bacterial strain. Research on optimizing their growth under various temperatures and pH conditions showed that both isolates grow best at 37°C. F1-B provides a better opportunity as a source of industrial enzymes because it can excrete amylase, urease, cellulose, and protease enzymes compared to F1-A, which can only produce amylase and protease enzymes. Nevertheless, F1-A can act as a potent antioxidant with an IC50 of 34.18 ppm compared to F1-B, which has an IC50 value of 292.31 ppm. The IC50 value of the F1-A isolate was not much different from the IC50 of quercetin, which was 12.50 ppm. The ability of F1-A as an antioxidant is also influenced by the results of phytochemical screening, which can contain more secondary metabolites than F1-B. These results highlight the potential of Pseudomonas strains as sources of industrial enzymes and natural antioxidants, warranting further investigation.